Dynamic Querying for Pattern Identification in Microarray and Genomic Data (2003) - Hochheiser, Harry; Baehrecke, Eric H.; Stephen M. Mount; Shneiderman, Ben (Institute for Systems Research Technical ReportsInstitute for Systems Research Technical Reports, 2005)
Data sets involving linear ordered sequences are a recurring theme in bioinformatics. Dynamic query tools that support exploration of these data sets can be useful for identifying patterns of interest. This paper describes the use of one such tool TimeSearcher - to interactively explore linear sequence data sets taken from two bioinformatics problems. Microarray time course data sets involve expression levels for large numbers of genes over multiple time points. TimeSearcher can be used to interactively search these data sets for genes with expression profiles of interest. The occurrence frequencies of short sequences of DNA in aligned exons can be used to identify sequences that play a role in the pre-mRNA splicing. TimeSearcher can be used to search these data sets for candidate splicing signals.
Keywords: Technical Report